2011
DOI: 10.1190/1.3640528
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dynamic interpretation from correlating well activity to frequently acquired 4D seismic signatures

Abstract: Quantitative 4D seismic interpretation can be successfully achieved by exploiting the causal link between the temporal variation in well activity and the 4D seismic signatures they induce. This is achieved by capturing in mathematical form the common interpretational practice of identifying the origin of dynamic signals in the 4D seismic volumes or maps on the basis of their association with a particular injector or producer. Thus, for example, a region of reservoir hardening (impedance increase) around a prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In some of the earlier efforts to use 4D data as a history-match constraint, Huang et al (1997Huang et al ( , 1998 and apply a map-based, semiautomated method. The seismic misfit is defined by the normalized crosscorrelation of a 4D attribute, such as impedance change, with the depth-averaged model prediction of that attribute.…”
Section: Computer-aided Model Updatingmentioning
confidence: 99%
“…In some of the earlier efforts to use 4D data as a history-match constraint, Huang et al (1997Huang et al ( , 1998 and apply a map-based, semiautomated method. The seismic misfit is defined by the normalized crosscorrelation of a 4D attribute, such as impedance change, with the depth-averaged model prediction of that attribute.…”
Section: Computer-aided Model Updatingmentioning
confidence: 99%
“…Also, whilst 4D seismic signatures controlled predominantly by pressure or saturation changes are to be preferred for our technique, mixed controlling factors prove more challenging. A possible solution is offered by the multiple survey well2seis technique of Huang et al (2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In general terms, it is understood that the 4D seismic signature is sensitive to changes of water and gas saturation and also pore pressure resulting from the injector and producer activity. Indeed, when calibrated with well historical data it has been shown that 4D seismic signatures can be quantitatively related to the water saturation and pressure changes in the reservoir (MacBeth et al 2006) or simply well activity through fluid volumes alone (Huang et al 2011). Following this development, here it is believed that the overall spatial variability of 4D seismic amplitudes can assess the continuity of the reservoir changes in particular fields, and in turn this can be used as an aid in quantitatively interpreting discontinuities attributed specifically to the faults.…”
Section: Methodsmentioning
confidence: 99%
“…PRM such as life of field seismic and ocean bottom cable will therefore enable the generation of the most stable and reliable correlation properties. According to studies over several fields from the North Sea (Huang et al, 2010(Huang et al, , 2011Huang and MacBeth, 2012;Yin and MacBeth, 2014), a minimum of five repeated seismic surveys are required for the technique to work. To ensure the robustness of the correlation product and reduce ambiguities, a threshold value is required for the W2S attribute.…”
Section: Methodologies the Well2seis Techniquementioning
confidence: 99%